Pfannenstiel Versus Maylard Incision for Gynecologic Surgery: A Randomized, Double-Blind Controlled Trial - Zinat Ghanbari; Bahareh Haji Baratali; Tahereh Foroughifar; Maryam Deldar Pesikhani; Mamak Shariat (Elsevier, 2009)
Objective: The aim of this study was to compare the effects of the transverse muscle-cutting Maylard incision and the Pfannenstiel incision for hysterectomies, in terms of postoperative complications, pain, and quality of life. Materials and Methods: This randomized, double-blind study compared two laparotomy techniques. All hysterectomies were performed for benign conditions. Eighty cases were randomly assigned to receive either Pfannenstiel or Maylard incisions. Measured intraoperative variables included volume of blood loss and duration of surgery. Postoperative variables included abdominal distension, postoperative pain, and quality of life. Results: Postoperative abdominal distension was significantly lower in the Maylard group (p = 0.004). There were no differences in intraoperative characteristics and duration of hospitalization, hemorrhage volume, or duration of surgery between the two groups. Conclusion: Hysterectomy performed via the Maylard incision was associated with the use of fewer additional analgesics than hysterectomy performed via the Pfannenstiel incision.